# Thread: Degenerate case of conic?

1. ## Degenerate case of conic?

The graph of each equation is a degenerate case. Identify the graph.

1.(x-2)^2-(x+3)^2=5(y+2) First I tried to simplify the equation
x^2-4x+4-x^2+6x+9=5y+10
0+2x+13=5y+10
2x-5y+3

Know according to my book I have to use the quadratic formula to take this equation and find the y.

My only issue is that my terms I got not a which would be y^2 all I have is "b" which is 5y and I do that I would up with y=5x which is wrong when I checked.

So I am confused on how to get the correct equation

2. Originally Posted by homeylova223
1.(x-2)^2-(x+3)^2=5(y+2) First I tried to simplify the equation
x^2-4x+4-x^2+6x+9=5y+10
Please try this again. "6x" and "9" have the wrong sign.

0+2x+13=5y+10
2x-5y+3
Know according to my book I have to use the quadratic formula to take this equation and find the y.
Your book did not tell you to solve this equation. It isn't an equation. It was!

Give it another go. See if it makes more sense.

3. So would it be 2x^2+2x-5y+13

Then would I use quadratic formula?

4. 1) You must be more careful. You had the sign correct on x^2. You fixed it all the way to broken. Don't do that.
2) Still not an equation. Equations have this: "=". Where did yours go?

(x-2)^2 - (x+3)^2 = 5(y+2)

(x^2 - 4x + 4) - (x^2 + 6x + 9) = 5y + 10

x^2 - 4x + 4 - x^2 - 6x - 9 = 5y + 10

x^2 - x^2 - 4x - 6x + 4 - 9 = 5y + 10

(x^2 - x^2) - (4x + 6x) + (4 - 9) = 5y + 10

Can you finish?

5. I got -10x-5=5y+10
-10x-15=5y
y=-2x-3